THE HYPOTHETICAL IMPLEMENTATION OF PRESUIT AND PRETRIAL DISCOVERY IN CIVIL LITIGATION IN BRAZIL - Pitta, Rafael Gomiero; Cambi, Eduardo Salomão (Revista de Direito Brasileira, 2021)
When analyzing quantitative data from the common law and civil law family systems of justice, the first striking comparative difference that draws attention is the number of cases solved in the early stages in the common law systems. In both England and the United States (USA) there is a high degree of efficiency in settling cases even before the trial stage. Although there is no such thing as Anglo-American law, especially given the distinctions that the English and North American models have shown in recent decades, the instruments used in the civil justice systems of these two countries are fertile ground for the study of possible solutions to be implemented in Brazil. This article presents the mentioned solutions of the so called Anglo-American system and elaborates a proposal for reforms able to introduce such methods in the Brazilian procedural system.